Camel Model And Financial Performance Of Commercial Banks In Nepal - Rohit Kumar Shrestha; Bindu Gnawali (SEIKO : Journal of Management & Business, 2022)
CAMEL is an acronym for five key performance parameters. C stands for capital adequacy, A for asset quality, M for management efficiency, E for earnings ability, and L for liquidity status. The objective of the study is to examine the relationship between CAMEL and Return on Asset (ROA) and the effect of CAMEL on the ROA (profitability) of Nepalese commercial banks. This study used a descriptive research design. The study applied a quantitative research technique. Secondary financial data from yearly reports are employed for analysis. In total, there are 26 commercial banks in Nepal. Nabil Bank Limited, Nepal Investment Bank Limited, Century Commercial Bank Limited, Nepal SBI Bank Ltd., Nabil Bank Limited, Everest Bank Limited, and Prabhu Bank have been chosen as samples, applying a lottery system, for the study out of a total population of 26. The study covered the years 2011/12–2020/21. More precisely, the data related to CAMEL variables and annual reports for each bank during the study period were obtained from their official websites. Correlation and regression were used for data analysis. A mixed correlation has been found between the CAMEL framework and ROA. Capital adequacy and asset quality have a significant and negative effect on ROA. However, earning ability has a significant positive effect on ROA. Management efficiency and liquidity status have an insignificant and negative effect on ROA. Thus, it can be generalized that ROA (profitability) is driven by internal factors i. e. earnings quality and also by capital adequacy, and assets quality and is not driven significantly by management efficiency and liquidity status in Nepalese commercial banks. The practical implication of this study is to add equity to the entire capital fund due to the significant and positive correlation and effect of earning ability with ROA. Banks can increase the amount of capital adequately considering capital structure that should be subject to a strict policy of banks. Banks should attempt to decrease the non-performing loan ratio by decreasing poor asset quality. Keywords: Asset Quality, Capital Adequacy- Earning Ability--Liquidity Status- Management Efficiency- Commercial Banks